Microstructural Changes in Snow During Equitemperature Metamorphism. - Brown, Robert L. (1997)
This grant was funded for the purpose of (1) developing the methodology for measuring the microstructural properties of snow, (2) performing a series of experiments to calibrate the theory developed to measure snow microstructure, and (3) determining in detail how the material microstructure changes with time under uniform temperature conditions. Microstructure includes such parameters as grain size, grain shape, bond size, neck length, pore size, and 3-D coordination number (number of bonds per grain). An essential part of the project included support for a visiting scientist from Japan, Atsushi Sato, who had developed specialized equipment for producing very fine-grained snow with predominantly spherical grain shape. This snow allowed us to perform the experimental part of the project with more precision than using natural snow. The small grain size was responsible for the rapid metamorphism, and the spherical gain shape greatly simplified the task of calibrating the software developed to measure the snow microstructure. The objectives of the grant have been achieved. A number of papers have either been published or are now being written, and the formulation developed by the PI and his doctoral student has been shown to be a very effective method of measuring microstructure.